The Impact of Acetyl-CoA and Aspartate Shortages on the N-Acetylaspartate Level in Different Models of Cholinergic Neurons - Marlena Zyśk; Monika Sakowicz-Burkiewicz; Piotr Pikul; Robert Kowalski; Anna Michno; Tadeusz Pawełczyk (MDPI AG, 2020)
N-acetylaspartate is produced by neuronal aspartate N-acetyltransferase (NAT8L) from acetyl-CoA and aspartate. In cholinergic neurons, acetyl-CoA is also utilized in the mitochondrial tricarboxylic acid cycle and in acetylcholine production pathways. While aspartate has to be shared with the malate-aspartate shuttle, another mitochondrial machinery together with the tricarboxylic acid cycle supports the electron transport chain turnover. The main goal of this study was to establish the impact of toxic conditions on N-acetylaspartate production. SN56 cholinergic cells were exposed to either Zn2+ overload or Ca2+ homeostasis dysregulation and male adult Wistar rats' brains were studied after 2 weeks of challenge with streptozotocin-induced hyperglycemia or daily theophylline treatment. Our results allow us to hypothesize that the cholinergic neurons from brain septum prioritized the acetylcholine over N-acetylaspartate production. This report provides the first direct evidence for Zn2+-dependent suppression of N-acetylaspartate synthesis leading to mitochondrial acetyl-CoA and aspartate shortages. Furthermore, Zn2+ is a direct concentration-dependent inhibitor of NAT8L activity, while Zn2+-triggered oxidative stress is unlikely to be significant in such suppression.